2018
DOI: 10.1371/journal.pone.0208277
|View full text |Cite
|
Sign up to set email alerts
|

Disease progression in mice exposed to low-doses of aerosolized clinical isolates of Burkholderia pseudomallei

Abstract: Mouse models have been essential to generate supporting data for the research of infectious diseases. Burkholderia pseudomallei, the etiological agent of melioidosis, has been studied using mouse models to investigate pathogenesis and efficacy of novel medical countermeasures to include both vaccines and therapeutics. Previous characterization of mouse models of melioidosis have demonstrated that BALB/c mice present with an acute infection, whereas C57BL/6 mice have shown a tendency to be more resistant to inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(58 citation statements)
references
References 83 publications
1
57
0
Order By: Relevance
“…In previous murine studies of melioidosis, usually one or two strains of B. pseudomallei were evaluated at the same time [30,31]. Furthermore, we have shown that the BALB/c mouse is very susceptible to infection to all the human clinical strains of B. pseudomallei examined, while the C57BL/6 mouse was significantly more resistant to infection to the same B. pseudomallei strains compared to the BALB/c mouse [29]. In the present report, we present the results of the BALB/c host immune response in chronically infected survivors after aerosol exposure to 10 separate human clinical strains of B. pseudomallei.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In previous murine studies of melioidosis, usually one or two strains of B. pseudomallei were evaluated at the same time [30,31]. Furthermore, we have shown that the BALB/c mouse is very susceptible to infection to all the human clinical strains of B. pseudomallei examined, while the C57BL/6 mouse was significantly more resistant to infection to the same B. pseudomallei strains compared to the BALB/c mouse [29]. In the present report, we present the results of the BALB/c host immune response in chronically infected survivors after aerosol exposure to 10 separate human clinical strains of B. pseudomallei.…”
Section: Introductionmentioning
confidence: 87%
“…This underscored the importance of getting a better understanding of different clinical strains of B. pseudomallei with their interaction with the host [25]. In a recent study a number of human clinical isolates of B. pseudomallei with documented low passage number were collected, and their virulence was evaluated in a 21 day median lethal dose (LD 50 ) study in a BALB/c murine model of melioidosis after aerosol exposure [29]. This study presented us with the unique opportunity to examine chronically infected BALB/c mice after the 21 day LD 50 aerosol study to ascertain if there were differences in the murine host response when many different clinical strains of B. pseudomallei were evaluated under similar conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have also noted a lowering of LD 50 values, in mice, when they compared the LD 50 results from 21‐day and 60‐day duration intraperitoneal infection studies with other strains of B. pseudomallei (Welkos et al ). Recent low‐dose, aerosol challenge studies comparing different clinical isolates of B. pseudomallei in BALB/c mice describe an LD 50 value of 25·1 CFU for K96243 (prototype strain), 0·99 CFU for HBPUB10134a and 0·35 CFU for MSHR5855 (Trevino et al ). A working hypothesis is that the virulence of NCTC 13392 falls somewhere between these strains.…”
Section: Discussionmentioning
confidence: 99%
“…A property of NCTC 13392 in particular, is that the LD 50 is likely to be inversely proportional to the study length due to its subacute characteristics, at low dose. The bacterial burden in the lungs and spleens of BALB/c mice infected with HBPUB10134a and MSHR5855 (delivered by aerosol with doses 6 CFU and 1·2 CFU respectively) is higher than mice infected with a low dose (8 CFU) of NCTC 13392 at day 10 pc, indicating that the infection caused by these other two strains, at low doses, becames established more quickly (Trevino et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation